KONFLIK SURIAH: AKAR MASALAH DAN DAMPAKNYA - A. Muchaddam Fahham; A.M. Kartaatmaja (Jurnal Politica, 2014)
Syrian conflict seemed to be an endless war, which has claimed more lives of civilians, causing thousand seekingrefuge and children losing their parents. Since March 2011, a large number of houses, infrastructure, and public service are devastated. This article describes the cause of the conflict, the actors, and the impacts of the continuity of the civilian war to Syria and international community. The writers conclude that conflict was not caused by sectarian factors, but political and economic interests of opposition groups and their supporting countries. There were three major warring parties, namely President Bashar and his loyalists, Syrian opposition group, and the jihadists. While, the number of refugees has reached 2.4 million, 75% of them are women and children, and there are also 4 million internally displaced people.